2015
DOI: 10.1016/j.stem.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA lncTCF7 Promotes Self-Renewal of Human Liver Cancer Stem Cells through Activation of Wnt Signaling

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent subtype of liver cancer, and it is characterized by a high rate of recurrence and heterogeneity. Liver cancer stem cells (CSCs) may well contribute to both of these pathological properties, but the mechanisms underlying their self-renewal and maintenance are poorly understood. Here, using transcriptome microarray analysis, we identified a long noncoding RNA (lncRNA) termed lncTCF7 that is highly expressed in HCC tumors and liver CSCs. LncTCF7 is required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
442
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 562 publications
(464 citation statements)
references
References 57 publications
8
442
1
1
Order By: Relevance
“…CD13 and CD133 are widely used as liver CSC markers (6,28 (29).We analyzed differential noncoding RNA transcripts in liver CSCs compared with non-CSCs and showed that lncTCF7 is highly expressed in liver CSCs, playing a critical role in the maintenance of liver CSC self-renewal (29).…”
Section: Resultsmentioning
confidence: 99%
“…CD13 and CD133 are widely used as liver CSC markers (6,28 (29).We analyzed differential noncoding RNA transcripts in liver CSCs compared with non-CSCs and showed that lncTCF7 is highly expressed in liver CSCs, playing a critical role in the maintenance of liver CSC self-renewal (29).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing amount of evidence has indicated that certain lncRNAs exhibit crucial roles in human cancers, acting as oncogenes or tumor suppressors (20,21). The lncRNA GAPLINC was previously reported to be overexpressed in gastric cancer and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NBAT-1 inhibits invasion and proliferation of breast cancer cells due to activation of Wnt signaling through inactivation of dickkopf Wnt signaling inhibitor 1 (DKK1) via recruitment of PRC2 (153). The last lncRNA to be discussed is lncTCF-7, which has been studied in HCC and shown to be involved in renewal of human liver cancer stem cells (CSCs) and HCC aggressiveness through promotion of EMT (154,155). Self-renewal of liver CSCs is mediated through recruitment of the SWI/SNF chromatin remodeling complex resulting in activation of Wnt signaling through lncTCF-7 (154).…”
Section: Metastasis-related Lncrnas: Category IImentioning
confidence: 99%
“…The last lncRNA to be discussed is lncTCF-7, which has been studied in HCC and shown to be involved in renewal of human liver cancer stem cells (CSCs) and HCC aggressiveness through promotion of EMT (154,155). Self-renewal of liver CSCs is mediated through recruitment of the SWI/SNF chromatin remodeling complex resulting in activation of Wnt signaling through lncTCF-7 (154). Activation of EMT in HCC cells is initiated by inflammatory cytokine IL6 which activates lncTCF7 expression through binding of STAT3 to the lncTCF7 promoter (155).…”
Section: Metastasis-related Lncrnas: Category IImentioning
confidence: 99%